Improving Reading and Calculation Ability through Audio Visuals Media in Indonesian Elementary School Student with Slow Learner: A Literature Study - Puspitasari, Fiolina Hana; Ediyanto; Efendi, Mohammad; Sunandar, Asep (Indonesian Journal of Disability Studies, 2021)
Learning media can be made using audio-visual media. Audio-visual media here is the media that conveys the message specifically to the senses of hearing and sight. The media has sound elements and image elements. Teachers who provide modifications to the media will make learning more interesting for students, especially if there are students with slow learner barriers in class. The slow learner is a learning barrier in children, which is characterized by a gap between the level of intelligence and academic ability that should be achieved. The use of audio-visual media is able to have a positive influence on the reading and numeracy skills of students with slow learners.